Komitmen dan kepuasan kerja pekerja di dua jenis organisasi - Nik Mutasim Abdul Rahman,; Nordin Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2001)
Employee commitment toward the organization and their job satisfaction vary with the type of organization, for example, whether the organization in question is public or private. Organizational theorists have shown that organizational effectiveness is closely associated with how human resource and their functions are organized. Effectively managed employees are expected to demonstrate higher levels of commitment toward the organization and higher levels of job satisfaction. A survey of 107 officers of a public organization (government agency) and 68 officers of a private sector organization (government agency) and 68 officers of a private sector organization was conducted. The findings show that, on the whole, employees of the public organization exhibited a higher level of affective and normative commitment than their counterpart in the private sector organization. The former also reported a higher level of job satisfaction. In addition, job satisfaction showed a positive and significant correlation with normative commitment in both types of organization